Peranan Manajemen Pendidik Dan Tenaga Kependidikan Di Sekolah Dasar - Damayanti Hasibuan, Ira; Nur Alaina Rambe, Sallima; Sofi Adinda, Nazla; Nurhayati, Suci; Nadhirah Mulyadi, Dea; Pratama Pane, Riswanda; Darmansah, Tengku (Faculty Of Education, 2023)
This research aims to determine the management role of educators and education personnel in elementary schools. This type of research is quantitative research using data collection carried out in natural conditions, accurate sources and data using interviews and documentation to obtain data in the research. The results of the research show that one of them is by developing aspects of educational personnel and supporting it by creating teacher management because this will advance the level of education in elementary schools and improve the quality of educational personnel. By forming professional educational staff, you can improve the quality of education that students receive in elementary schools.